Evaluating the effectiveness of shariah risk management in Malaysian Islamic financial institutions - Ghani, Nur Laili Ab; Ariffin, Noraini Mohd; Rahman, Abdul Rahim Abdul (Asian Economic and Financial Review, 2025)
Effective Shariah risk management is crucial for Islamic Financial Institutions (IFIs) in ensuring robust identification and mitigation of risks associated with Shariah non-compliance. Incidents related to Shariah non-compliance in Islamic financial activities can lead to a loss of trust and credibility among stakeholders. Although IFIs have implemented Shariah risk management functions to address these risks, their effectiveness remains largely unassessed. This research explores the effectiveness of Shariah risk management in IFIs in Malaysia. A quantitative research methodology was adopted, utilizing a survey questionnaire to collect data from a representative sample of all 47 IFIs in the country. The measurement was based on the Shariah Governance Policy Document (SGPD) issued by Bank Negara Malaysia (BNM), which all IFIs in Malaysia are required to implement. The study found that most IFIs have implemented a moderately effective level of Shariah risk management functions and processes. This research provides valuable insights into the effectiveness of Shariah risk management in IFIs and emphasizes the importance of establishing robust control functions and fostering a culture of Shariah compliance to improve the management of Shariah non-compliance risks.